Antioxidant Activity of Mytilus galloprovincialis and Ruditapes philippinarum - Sehat Çolakoğlu; Gülen Türker; İlknur Ak; Fatma Çolakoğlu (Turkish Journal of Agriculture: Food Science and Technology, 2019)
This study reports on the evaluation of the antioxidant of ethanolic extracts of Mytilus galloprovincialis and Ruditapes philippinarum collected from the Marmara Sea. The antioxidant activity of the two bivalve species was evaluated using the 2,2-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging method. The total carotenoid contents were also determined. In the DPPH method, all extracts exhibited low radical scavenging activity when compared to the standards used, i.e. -tocopherol and butylated hydroxytoluene (BHT) with the inhibition percentage in the range of 35.87±0.05 – 36.27±0.02%. In particular, M. galloprovincialis exhibited the highest radical scavenging activity with an IC50 value of 29.55±0.02 mg/g Ext. However, there are no statistically significant differences in the IC50 values of two species. The highest total carotenoid content was found in M. galloprovincialis as 1.13±0.02 µg/g sample. The statistically significant differences were found in total carotenoid contents of two bivalves. In this study in M. galloprovincialis was also found to be high in carotenoid content, while R. philippinarum was found to be almost nonexistent. More detailed studies are needed to determine relationship between the bioactive compounds of crustaceans and their antioxidant activities, distributed in our country.